Effect of Slag and Recycled Materials on the Performance of Hot Mix Asphalt (AC-BC) - Bethary, Rindu Twidi (Institut Teknologi Bandung, 2019)
The limitations of road construction materials require alternative materials such as asphalt recycling and utilization of waste potential such as steel slag for aggregate substitutes. In this study, there were tests for slag characteristics and reclaimed asphalt pavement (RAP) then continued with a marshall test to determine the optimum asphalt content (OAC). The nine mixtures planned in this study consist of 10-30% Slag combined with 10-30% RAP with Reclamite as a rejuvenating material. Using a combination of RAP, there is a decrease in the mixing and compaction temperature of 20°C compared to the conventional hot mix. Test results on hot mix asphalt using a combination of RAP and slag generate an increase of 10-30% each using a combined gradation and volume correction. Test result in heat asphalt mixture by using RAP and slag combination with additional of 10-30% each using correction of volume and combined gradation. For the hot mix asphalt with RAP10 and SLAG 10-30 (HMAR10S10-30), the OAC value is 5.83%, 5.95%, and 5.38%, and for the hot mix asphalt with RAP20 and SLAG 10-30 (HMAR20S10- 30), the OAC value obtained is 5.90%, 5.60%, and 5.95%, and for the hot mix asphalt with RAP30 and SLAG 10-30 (HMAR30S10-30), the OAC value is 5.55%, 5.60 %, and 5.33%.